Association of sedentary behavior and early engagement in physical activity with low back pain in adolescents: a cross-sectional epidemiological stud﻿y - Lemes, Ítalo Ribeiro; Oliveira, Crystian Bitencourt; Silva, Gabriela C. R. [UNESP]; Pinto, Rafael Zambelli; Tebar, William R. [UNESP]; Christofaro, Diego G. [UNESP] (Springer Nature, 2022)
Purpose: To investigate the association of sedentary behavior and physical activity from childhood to adolescence with prevalence of low back pain in adolescents. In addition, we also explored whether sleep quality influences this association. Methods: This is a cross-sectional epidemiological study. Participants (aged 10–17 years) were recruited from public and private schools in Brazil. Sedentary behavior and previous and current engagement in physical activity were assessed through questionnaires. Low back pain and sleep quality were assessed by the Nordic questionnaire and Mini-Sleep Questionnaire, respectively. Sex, age, body mass index, abdominal obesity, socioeconomic status and sleep quality were used as potential confounders. Binary logistic regression models were used to generate values of odds ratio (OR) and 95% confidence intervals (95%CI). Results: A total of 1,001 (44,5% boys; n = 446) were included. Overall prevalence of low back pain was 18%, with higher rates among inactive and sedentary participants. Physical inactivity from childhood to adolescence in combination with high sedentary behavior doubled the likelihood of having low back pain (OR = 2.40 [95%CI: 1.38–4.18]), independent of potential confounders. Sleep quality attenuates, but not eliminates, this association (OR = 2.19 [95%CI: 1.25–3.84]). Conclusion: Being inactive from childhood to adolescence in combination with high sedentary behavior is associated with low back pain in adolescents. Sleep quality seems to attenuate, but not eliminate, this association.
Keywords: Exercise; Lifestyle; Musculoskeletal health; Sitting; Sleep